The Influence of Competence and Workload on the Quality of Services at the Aeng Towa Health Center, Takalar Regency - Sudarmini Syam; Nurmadhani Fitri Suyuthi; Mujahid (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
The purpose of this study was to determine the influence of Competence and Workload together on the Quality of Services at the Aeng Towa Health Center, Takalar Regency. This study is a quantitative study based on the philosophy of positivism, which uses empirical data to test the hypothesis. The sample used was 71 respondents taken from employees of the Aeng Towa Health Center, Takalar Regency. The determination of the sample used was the total sample or saturated sample by making all populations as samples because the number was smaller and below 100. The analysis technique used was multiple linear regression analysis and statistical tests using SPSS. Before conducting multiple linear regression analysis, research instrument testing and classical assumption tests were carried out for the accuracy of the regression analysis results. The data sources used in this study were primary data and secondary data. The data collection method used the questionnaire and documentation methods. The results of the study indicate that competence and workload simultaneously affect the quality of service at the Aeng Towa Health Center, Takalar Regency. The results of this study also provide a strong basis for policy development at the health center. The combination of high competence and well-managed workload creates a positive synergy that has a significant impact on service quality. When administrative staff have adequate competence and appropriate workload, they can carry out their tasks more efficiently, which ultimately improves the quality of service they provide.